A formação acadêmica do enfermeiro para o SUS na percepção de docentes e discentes da faculdade de enfermagem/UERN - Costa, Roberta Kaliny de Souza (2008)
The model of attention to health in Single Health System (Sistema Único de Saúde SUS) presupposes a human-resources policy which prepares professionals of health to guide the services and sanitary practices. The nurse, a member of health staff, takes over an important role in implementation of principles and standards of SUS, being its professional formation necessary to labor organization in this purpose. In this way this study objectifies to analyse the process of formation of the male nurse in the Politic-Pedagogical Project (Projeto Político-Pedagógico PPP) in the perception of learning and teaching of the Faculty of nursing FAEN of the University of The Rio Grande do Norte State UERN. It treats about a descriptive-exploratory study with qualitative and quantitative approach carried out with learning and teaching of the graduation nursing course. In the field research carried out between the months of november, 2006 and february, 2007, were used like instruments the documental research below PPP´s, structured interview directed to the learning and the closed questionnaire applied to the students of eighth and ninth semesters of graduation course. The results of data about the questionnaires elaborated according to National Curricular Patters (Diretrizes Curriculares Nacionais DCN) and the Instrument of Evaluation Course of Graduation MEC were organized according to six lists about the profile of the learning and teaching that participate of the research; of the didactical-pedagogical organization and PPP´s objectives to the just-graduates person to the didactical-pedagogical curriculum organization. For considering the interviews it was adopted thematic analysis of content discribed in lexical analysis by informatical program ALCESTE which provided the organization of the material in five categories: daily problems of SUS consolidation versus nurse formation, dichotomies about FAEN´s nursing course of curriculum versus principles of integralization of graduating process, the just-graduated one from FAEN and its professional insertion united to SUS politic-pedagogical project and the concern about the overcoming of dichotomies of graduation process abilities and necessary competences to the SUS performing nurse. The analysis of informations deriving from documental performance and field research resulted on the verification that, in spite of good intentions, the implementation strategies showed themselves fragile to cope with the rendering of expressed ideal on PPP. There is still a great gap between what´s thought as innovating graduating process and what´s being really implemented